The gender equality in the Spanish cooperation and the initiative Marca España. Boardings and inconsistencies in times of crisis - Julia Espinosa Fajardo (Investigaciones Feministas, 2015)
Since the nineties, human development and gender equality have become two central priorities of the international agenda and for the Spanish State. However, in the current international economic and financial crisis, and linked to agenda of macroeconomic stability and fiscal austerity set in rich countries, the promotion of human development seems to be on a second level. In this scenario, the progress made internationally in the promotion of gender equality through public policies is also at risk of being seriously affected. In the case of the foreign and cooperation policy of Spanish State, the official development aid is cut back to figures as in early eighties and, at the same time, the ‘Marca España’ initiative takes centrality. And, all of this in a scenario where we are attending a marginalization of gender content in the public agenda. This article looks at if there is a commitment to a pro-gender equality development according to the international commitments of the Spanish State. It specifically analyses if this commitment exists in the ‘Marca España’ initiative and in the Spanish cooperation policy for the period 2008-2014. Due to the impact of both policies in the development of Southern countries, it investigates whether gender equality is included or excluded as an objective in these policies, the different approaches adopted in this regards and the economic and institutional resources to promote gender equality. All this aims to identify possible transformations occurring in the analysis period, marked by the international crisis and the change of government, and the inconsistencies between the two policies that can limit the impact of the pro-gender equity efforts.